PEMAKZULAN PARK GEUN-HYE SEBAGAI PRESIDEN KOREA SELATAN - Adinda Sulistia; Muharjono Msi (Jurnal Paradigma, 2018)
Since October 2016, in South Korea there was a political instability that caused theimpeachment of Park Geun-hye as the president of South Korea. Park supposed to endedher term in early 2018, however, in March 2017, Park was removed from the office andimprisoned. This scandal also known as the Confidate Scandal between Park Geun Hyeand her close friend, Choi Soon Sil, and also involves some of her closest people includingmany large conglomerates in South Korea or known as Chaebol. This scandal has causeddisappointment to the people of South Korea, resulting hundred of thousands doing a seriesof demostration demanding her removal from power.This study aims to discuss the background of the impeachment of Park Geun Hyewith the data based on the methodology of Library Research. Especially in the period from2016 to 2017 and also based on others data that relevant to this study. This study describethe processes in the parliament, the elections and the impeachment. As well as analyzingthe factors that caused the impeachment of Park Geun Hye.